Paediatric perineal and genital burns: A decade of insights and implications - Rakib H. Sheikh; Avinesh Chelliah; Rachel D’Cruz; Andrew J.A. Holland; Torey Lawrence (Burns Open, 2025)
Background: Perineal, genital and buttock burns are uncommon, but their consequences can be severe. Methods: A decade-long (2014–2024) retrospective review was conducted on paediatric patients referred to the Children’s Hospital at Westmead (CHW), New South Wales with perineal, genital and buttock (PGB) burns. Results: A total of 252 patients were identified with perineal, genital and buttocks burns. Most burns occurred as part of more extensive injuries involving the lower limbs, with only 10.7 % classified as isolated PGB burns. Adequate first aid was administered in 90.5 % of cases, either at the scene or upon hospital admission. Thirty two percent (n = 81) required skin grafting, including 42 cases involving the PGB area and 41.7 % needed an indwelling urinary catheter (IDC). Conclusions: Even though PGB burns are rare, but complications can include urinary tract infections, hypertrophic scarring, and the need for ongoing scar management. These findings emphasise the importance of early intervention and specialised care in managing PGB burns in children.